Análisis del costo-volumen-utilidad y su incidencia en la rentabilidad de la florícola Dazarina Flowers, ciudad de Latacunga, período 2019-2022 - Osorio Santos, Adriana Stefania (2024)
ABSTRACT: The present research project called "Analysis of the cost-volume-profit and its impact on the profitability of the floriculture Dazarina Flowers, city of Latacunga, period 2019-2022", had the purpose of collecting the necessary information to meet the objectives of examining the fixed and variable costs and subsequently evaluate the economic results obtained during the periods mentioned so that it is feasible to know if the floriculture has been profitable or not when going through the different crisis scenarios. In the first chapter, Dazarina Flowers' problem statement is established, along with the problem's formulation, justification, and the delineation of its general and specific objectives. The theoretical underpinnings and pertinent history of the Cost-Volume-Utility Analysis are developed in the second chapter, along with fundamental ideas that aided in the project's development. The third chapter details the methodology that will be used, which consists of the research methods, research approach, types of research, research design, population and sample, data collection techniques and instruments, through which detailed information will be collected from Dazarina Flowers. In the fourth chapter, the results obtained from the cost-volume-utility analysis are presented, fulfilling the stated objectives. And finally, in chapter five the conclusions are presented to respond to each objective, as well as the recommendations directed to the floriculture Dazarina Flowers Keywords: Break-even point, profitability, fixed costs, variable costs.